Avaliação neurologica de recem-nascidos pre-termo acometidos por hemorragia periventricular-intraventricular - Stopiglia, Monica Carvalho Sanchez (1997)
Orientador: Maria Valeriana Leme de Moura Ribeiro, Sergio Tadeu Martins Marba